Mixed chimerism in haemoglobinopathies: from risk of graft rejection to immune tolerance. Issue 3 (March 2014) - Andreani, M.; Testi, M.; Lucarelli, G.
Abstract Mixed chimerism (MC), the simultaneous presence of both host‐ and donor‐derived cells in the recipient, is observed in a large proportion of patients after haematopoietic stem cell transplant (HSCT) to treat haemoglobinopathies. Detected early after transplantation, MC often moves towards complete chimerism, although sometimes it may evolve into graft rejection, especially if the proportion of donor cells is very low. However, some patients develop stable MC, defined as persistent when donor‐ and host‐derived cells coexist for periods longer than 2 years after HSCT. Patients with persistent mixed chimerism (PMC) do not require additional red blood cell support and, regardless of the presence in some cases of an extremely low percentage of donor‐derived nucleated cells in the bone marrow, their condition is clinically controlled by an incomplete but functional graft, as they express a two‐ to fivefold enrichment of donor‐derived mature erythrocytes in the peripheral blood. These findings have tremendous implications not only in the context of allogeneic HSCT but also in the design of gene therapy trials based on the autologous transplantation of genetically modified CD34+ cells. Recent studies have shown that durable allograft tolerance has been achieved by induction of haematopoietic chimerism in clinical kidney transplantation, showing the involvement of regulatory T cells. Similarly, it has been shown that the regulatory T cells play a pivotal role in promoting and maintaining immune tolerance in patients that develop a status of PMC after HSCT for Thalassemia.